Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
TAVARES, MARCOS, MENDONÇA, JOEL BRAGA DE JR. (2022): Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean. Zootaxa 5146 (1): 1-129, DOI:10.11646/zootaxa.5146.1.1, URL: http://dx.doi.org/10.11646/zootaxa.5146.1.1